Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/edt.12092
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injuries in Turkish children, Istanbul

Abstract: In childhood, a correct diagnosis may affect the management methods and prevent the occurrence of complications after treatment for traumatic dental injuries. Therefore, continuing education programs offering the latest updates in the management of traumatized teeth should be provided for dental and medical practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1
34

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 27 publications
9
40
1
34
Order By: Relevance
“…This seems to be related to the start of development of motor skills and the accidents during this developmental stage 28 . Nonetheless, other studies that include both dentitions refer that, contrary to what this investigation reports, the teeth suffering most trauma were the permanent maxillary central incisors 11,27 . The maxillary central incisors are the set of teeth most affected by trauma probably due to their earlier eruption, being predisposed to a longer exposure period 1 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This seems to be related to the start of development of motor skills and the accidents during this developmental stage 28 . Nonetheless, other studies that include both dentitions refer that, contrary to what this investigation reports, the teeth suffering most trauma were the permanent maxillary central incisors 11,27 . The maxillary central incisors are the set of teeth most affected by trauma probably due to their earlier eruption, being predisposed to a longer exposure period 1 .…”
Section: Discussioncontrasting
confidence: 99%
“…The majority of traumatic dental lesions occurred in the maxillary central incisors (primary and permanent) 1,[11][12][13][14][15][18][19][20][27][28] . However, the primary teeth, specifically the primary maxillary central incisors (right or left), were the most affected by trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with many investigations, it was found that the most common injured teeth were maxillary central incisors (1,8,(11)(12)(13)(14)(15)(16)20,24). This might be associated with the position of these teeth, which exposes them to direct traumatic force.…”
Section: Akyıldız Et Al Dental Trauma Of Children In Aydınsupporting
confidence: 86%
“…Since the most frequently used study method is the classification of Andreasen et al (18), which is also adopted by the World Health Organization, we referred to it for our study. Several of the studies reported that boys faced with trauma more common than girls (8,(13)(14)(15)(16)19). It has been thought that boys had a more tendency towards contact sports and violent behaviors (13,14,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation